Ethics - "Sachdev, Kumar Neeraj" (Delhi, 2005)
The Author Examines In The Book The Intricate Relation Between Morality And Human Life. In The Course Of His Examination He Argues That The Liberal Moral Theory Is Inadequate To Accommodate The Idea Of A Moral Person Because It Forces A Person To Accept
Keywords: Ethics